Development of photocatalytic self-cleaning surfaces on 316 stainless steel - Ong, Jun Hui (Nanyang Technological University, 2023)
Surfaces that are able to keep themselves clean with the aid of water are described as self-cleaning surfaces. Such surfaces have drawn a lot of attention due to their numerous applications in food, aerospace, manufacturing and other industries. Self-cleaning for metals and alloys is usually achieved by creating hydrophobic textured surfaces. However, such surfaces obtained by texturing are unstable as their wettability changes over time. An alternative to create such hydrophobic surfaces is through the photocatalytic effect where a semiconductor material is able to generate radicals to remove organic contaminants upon the illumination of UV light.